Relative abundance, and activity patterns of mammals at Chimalapa´s forest, Oaxaca, Mexico - Lira-Torres, Iván; Briones-Salas, Miguel (Instituto de Ecología, A.C., 2012)
The Chimalapa´s Forest at the southeast of Mexico is one of the priority regions for conservation. There are preserved areas of tropical forests that have not been explored previously. The study of populations of mammals that live in this region, as well as the analysis of relative abundance and activity patterns can help us to understand the functioning of the ecosystem. Using the technique of camera- traps, we determine the relative abundance and activity patterns of medium and large mammals at Chimalapa´s Forest, Oaxaca. There were two photographic sampling periods: the 2009 dry season and the 2010 rainy season using a total of 54 camera- traps in each period. The total effort was 4,860 trapdays; we recorded 22 species, 20 medium and large mammals, and two birds. The 50% of the species are included in a category of endangered by national and international laws. The most abundant species were Cuniculus paca, Tayassu pecari, Dasyprocta mexicana, Pecari tajacu, Tapirus bairdii and Dasypus novemcinctus, whereas the less abundant was Urocyon cinereoargenteus. There were three types of patterns of activity: Nocturnal-twilight; with 13 species, diurnal-nocturnal-twilight (24 hrs); three species, and five diurnal species. Our results are a contribution to the planning of the management and the conservation of the mammals at this important region of Mexico.